2007
DOI: 10.2527/jas.2006-318
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous cellulase supplementation on microbial growth and ruminal fermentation of a high-forage diet in Rusitec fermenters1

Abstract: Two incubation runs were carried out with a Rusitec system to investigate the effects of 2 exogenous pure cellulases on ruminal microbial growth and fermentation of a 70:30 grass hay:concentrate (DM basis) substrate. The substrate was sprayed with buffer (control; pH = 6.5), a cellulase from Trichoderma longibrachiatum (TRI), a cellulase from Aspergillus niger (ASP), or a 1:1 mixture of both cellulases (MIX) 24 h before being placed in the fermenters. Enzymes were applied at a rate of 30 endoglucanase units/g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 25 publications
8
36
0
1
Order By: Relevance
“…Wang et al (2001) reported that applying an enzyme preparation to the feed 24 h before feeding increased barley grain DM disappearance after 48 h of incubation, but had no effect when enzymes were directly infused into the fermenters. Although Giraldo et al (2007a) have shown an increase in 48 h DM, NDF and ADF disappearance in the Rusitec with enzyme application to a forage-based diet 24 h before feeding, additional work by this same group observed these responses after 6 and 24 h of incubation, but not after 48 h (Giraldo et al, 2007b). In addition, Wang et al (2001) did not observe higher DM or NDF disappearance of alfalfa hay after 48 h of incubation when enzymes were applied 24 h before feeding.…”
Section: Rusitecmentioning
confidence: 85%
See 1 more Smart Citation
“…Wang et al (2001) reported that applying an enzyme preparation to the feed 24 h before feeding increased barley grain DM disappearance after 48 h of incubation, but had no effect when enzymes were directly infused into the fermenters. Although Giraldo et al (2007a) have shown an increase in 48 h DM, NDF and ADF disappearance in the Rusitec with enzyme application to a forage-based diet 24 h before feeding, additional work by this same group observed these responses after 6 and 24 h of incubation, but not after 48 h (Giraldo et al, 2007b). In addition, Wang et al (2001) did not observe higher DM or NDF disappearance of alfalfa hay after 48 h of incubation when enzymes were applied 24 h before feeding.…”
Section: Rusitecmentioning
confidence: 85%
“…To determine daily volatile fatty acids (VFA) and NH 3 -N production, effluent was collected daily from day 9 to 11 in flasks containing 20 ml of 3.66 M H 2 SO 4 (20%, vol/vol; Giraldo et al, 2007b). Subsamples of the fermenter effluent (2.5 ml) were taken directly from the effluent flask at the time of feed-bag exchange and were placed in screw-capped vials containing 0.5 ml of 25% (wt/wt) metaphosphoric acid and stored at −20°C until VFA analysis.…”
Section: Experiments 2 Determination Of Efe On Ruminal Digestionmentioning
confidence: 99%
“…Mao et al (2013) found that the addition of cellulase and xylanase increased the numbers of total bacteria and Fibrobacter succinogenes in the incubation medium in vitro and thereby improved the substrate fermentation. Giraldo et al (2007) showed that treatment of poor quality forage or forage-based diets with exogenous enzymes stimulated the initial phases of microbial colonization in the rumen, and this is recognized as one mode of action of enzymatic products . The addition of fibrolytic enzymes facilitates the access of microorganisms to feed components enabling a faster microbial growth.…”
Section: Discussionmentioning
confidence: 99%
“…Physical treatments include heating (Brandt and Klopfenstein 1986) and varying the particle sizes (Schadt et al 2012). On the other hand, chemical treatments are the best used methods, including the use of enzymes such as cellulases and xylanases (Giraldo et al 2007). The ruminant diet is based on forage consumption, in ruminant production systems, anything that improves the nutritional value of forage with a high fiber concentration and low digestibility can increase the productivity of ruminants (Giraldo et al 2007).…”
Section: Food Transformation Before Consumptionmentioning
confidence: 99%
“…On the other hand, chemical treatments are the best used methods, including the use of enzymes such as cellulases and xylanases (Giraldo et al 2007). The ruminant diet is based on forage consumption, in ruminant production systems, anything that improves the nutritional value of forage with a high fiber concentration and low digestibility can increase the productivity of ruminants (Giraldo et al 2007). Researchers have shown that supplementing the cattle diet with fibrolytic enzymes significantly improves the use of nutrients and increases ruminant efficiency.…”
Section: Food Transformation Before Consumptionmentioning
confidence: 99%